Analisis Penerapan Pembuktian Terbalik dalam Kasus Tindak Pidana Korupsi: (Studi Perkara Nomor: 22/Pid.Sus-TPK/2018/PN.Gto) - Arhjayati Rahim; Madinah Mokobombang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
Evidence in criminal cases is generally borne by the public prosecutor. This is different from the criminal case of corruption, in addition to being proven by the public prosecutor, the defendant also has the right to prove that he did not commit a criminal act of corruption. This study aims to determine the arrangement of the shifting burden of proof system in cases of corruption and the application of the shifting burden of proof system in cases of corruption in Decision Number: 22/Pid.Sus-TPK/2018/PN.Gto. This type of research is a literature analyzed with a normative juridical approach. The results of the research show that the Decision Number: 22/Pid.Sus-TPK/2018/PN.Gto, seen from the evidence that in terms of the application of reverse evidence, the defendant exercised his right to carry out shifting burden of proof. However, the defendant did not prove that the property he had obtained was not the result of a criminal act of corruption, even though it was his obligation to prove this, so that the right to shifting burden of proof evidence was not fully utilized by the defendant.